Tales for the dying : the death narrative of the Bhāgavata-Purāṇa - Jarow, Rick (SUNY series in Hindu studies., 2003)
"This book discusses how images of dying in the Bhagavata-Purana relate to issues of language and love in the religious imagination of India. Drawing on insights from studies in myth, literary semiotics, and depth psychology, as well as from Indian commentarial and aesthetic traditions, the author examines the power of myth and narrative (storytelling or hari katha) and shows how a detailed awareness of the Puranic imagination may lead to a revisioning of some long-held presuppositions around Indian religious attitudes toward dying. By casting Vaisnava bhakti traditions and Puranic narrative in a fresh light, the mythic imagination of the Puranas takes its place on the stage of contemporary discourse on comparative mythology and literature."--Jacket